A Comparative Study of Various Flow Instability Criteria in Processing Map of the Powder Metallurgy High Speed Steel. Issue 1 (March 2021) - Liu, Zhaozhao; Wang, Miao; Liu, Yanhui
Abstract: The deformation behavior of the 1.15C-4.00Cr-3.00V-6.00W-5.00Mo powder metallurgy high speed steel in hot working processes was investigated by the isothermal compression tests carried out at the temperature of 1000-1150°C and the strain rate of 0.001-1.0s −1 with the height reduction of 60%. The processing maps were constructed, identification of the instability regions and optimization of hot deformation parameters. Different types of instability criteria of PRASAD, MALAS, GEGEL, MURTY and SEMIATIN were compared. It was found that the hot working process of the steel can be carried out safely in the domain of 1040-1130 °C/0.01-1.0 s −1 . Furthermore, the temperature and the strain rate had a great effect on microstructures. To obtain a homogeneous microstructure with fine grain, the hot working process should be carried out under the condition of 1050-1100 °C/0.01-0.06 s −1 .